Modernisation, smoking and chronic disease: Of temporality and spatiality in global health. (May 2016) - Reubi, David
Abstract: This article explores the spatio-temporal logics at work in global health. Influenced by ideas of time–space compression, the global health literature argues that the world is characterised by a convergence of disease patterns and biomedical knowledge. While not denying the influence of these temporalities and spatialities of globalisation within the global health and chronic disease field, the article argues that they sit alongside other, often-conflicting notions of time and space. To do so, it explores the spatio-temporal logics that underpin a highly influential epidemiological model of the smoking epidemic. Unlike the temporalities and spatialities of sameness described in much of the global health literature, the article shows that this model is articulated around temporalities and spatialities of difference. This is not the difference celebrated by postmoderns, but the difference of modernisation theorists built around nations, sequential stages and progress. Indeed, the model, in stark contrast to the 'one world, one time, one health' globalisation mantra, divides the world into nation–states and orders them along epidemiological, geographical and development lines.